Uptake of endoscopic screening for gastroesophageal varices and factors associated with variceal bleeding in patients with chronic hepatitis C infection and compensated cirrhosis, 2005‐2016: a national database linkage study. Issue 4 (3rd June 2019) - McDonald, Scott A.; Barclay, Stephen T.; Hutchinson, Sharon J.; Stanley, Adrian J.; Fraser, Andrew; Dillon, John F.; Innes, Hamish A.; Peters, Erica; Kennedy, Nicholas; Bathgate, Andrew; Bramley, Peter; Morris, Judith; et al.
Summary: Background: Primary measures for preventing morbidity and mortality associated with bleeding gastroesophageal varices in cirrhotic patients include endoscopic screening. Aim: To identify factors associated with (a) screening and (b) first hospital admission for variceal bleeding among cirrhotic hepatitis C virus (HCV) patients attending specialist care in Scotland. Methods: The Scottish Hepatitis C Clinical Database was linked to national hospitalisation and deaths records to identify all chronic HCV patients diagnosed with compensated cirrhosis in 2005‐2016 (n = 2741). The adjusted odds of being screened by calendar year period were estimated using logistic regression, and the adjusted hazard ratio (HR) of a first variceal bleed using Cox regression. Results: About 34% were screened within the period starting 12 months before and ending 12 months after cirrhosis diagnosis. The proportion screened was stable in 2005‐2010 at 42%, declining to 37% in 2011‐2013 and 26% in 2014‐2016. Odds of screening were decreased for age‐groups <40 (OR = 0.61, 95% CI: 0.48‐0.77) and 60+ years (OR = 0.67, 95% CI: 0.48‐0.94), history of antiviral therapy (OR = 0.70, 95% CI: 0.55‐0.89), and cirrhosis diagnosis in 2014‐2015, compared with 2008‐2010 (OR = 0.67, 95% CI: 0.52‐0.86). Compared with 2008‐2010, there was no evidence for an increased/decreased relative risk of a first variceal bleed in any other period, but viral clearance was associated with a lower risk (HR = 0.56, 95% CI: 0.32‐0.97). Conclusions: Overall screening uptake following cirrhosis diagnosis was low, and the decline in recent years is of concern. The stable bleeding risk over time may be attributable both to ongoing prevention initiatives and to changing diagnostic procedures creating a patient pool with milder disease in more recent years.